ANALISIS KOMPETENSI PEMBUATAN BATIK CAP BERDASARKAN TUNTUTAN STANDAR KOMPETENSI KERJA NASIONAL INDONESIA PADA PESERTA DIDIK SMK NEGERI 14 BANDUNG - Kusmawati, Retno (2016)
The efforts to improve the quality of human resources (HR) conducted by the Indonesian government to face the MEA is to establish the SKKNI (Indonesian National Competency Work Standard). SMK Negeri 14 Bandung is one of the vocational school that is responsible to produce qualified human resources and suitable to the global labor market. The competency of batik production developed in the vocational school should refer to the SKKNI. This research aims to analyze the competency of stamped batik production based on the SKKNI of SMK Negeri 14 Bandung studentsinvolving (1) the preparation phase which consists of: stamping, dab staining, and pelorodan (removing the ink from the material), (2) the implementations phase consists of: stamping, dab staining, and pelorodan, and (3) finishing phase consists of: completion of the stamping, dab staining, and pelorodan. This research is using descriptive analysis method. The sample used in this study is the total sample are all students of class XI DPK Textile Craft totaling 50 people. Data collection technique used in this research are documentation study, checlist, and interview. The results of the analysis showed that: (1) the preparation phase in the batik production is at a very appropriate criteria, (2) the implementation phase in the batik production is at the appropriate criteria, and (3) the finishing phase in the batik production is at the appropriate criteria. Overall, the production of stamped batik based on SKKNI in SMK Negeri 14 Bandung is at the appropriate criteria. The suggestion based on the results of this research is the teachers should improve the competency of stamped batik production based on SKKNI specially in the implementation phase to fit the demands of SKKNI and be assertive to the students to be aware of using safety equipment ;--- Upaya peningkatankualitassumberdayamanusia (SDM) yang dilakukanolehpemerintah Indonesia menghadapi MEA yaitudenganmenetapkanStandarKompetensiKerjaNasional Indonesia (SKKNI).SMK Negeri 14 Bandung merupakansalahsatu SMK yang berkewajibanmencetak SDM yang berkualitasdansesuaidengantuntutanpasarkerja global.Kompetensipembuatan batik yang di kembangkan di SMK seharusnyamengacupada SKKNI.Penelitianinibertujuanuntukmenganalisiskompetensipembuatan batik cap berdasarkantuntutan SKKNI padapesertadidik SMK Negeri 14 Bandung meliputi (1) Tahappersiapan yang terdiridari: persiapanpengecapan, pewarnaancolet, danpelorodan, (2) Tahappelaksanaan yang terdiridari: pengecapan, pewarnaancolet, danpelorodan, dan (3) Tahappenyelesaian yang terdiridari: penyelesaianpengecapan, pewarnaancolet, danpelorodan. Penelitianinimerupakanpenelitiandenganmenggunakanmetodedeskriptifanalisis.Sampel yang digunakanpadapenelitianiniadalahsampel total yaituseluruhpesertadidikkelas XI DPK KriyaTekstil yang berjumlah 50 orang. Teknikpengumpulan data menggunakanstudidokumentasi, pengisiandaftarchecklist, danwawancara.Hasilanalisismenunjukanbahwa: (1) Tahappersiapandalampembuatan batik cap beradapadakriteriasangatsesuai, (2) Tahappelaksanaandalampembuatan batik capberadapadakriteriasesuai, dan (3) Tahappenyelesaiandalampembuatan batik capberadapadakriteriasesuai. Secarakeseluruhanpembuatan batik cap berdasarkantuntutanSKKNI di SMK Negerei 14 Bandung beradapadakriteriasesuai. Rekomendasidaripenelitianiniyaituhendaknya guru meningkatkankompetensipembuatan batik cap berdasarkan SKKNI terutamapadatahappelaksanaanpembuatan batik cap agar sesuaidengantuntutan SKKNI dan ketegasan kepada peserta didik terhadap kesadaran mengenakan alat K3 kerja.